Ultrahigh performance polylactide achieved by the design of molecular structure. (August 2021) - Li, Peng; Zhang, Wei; Kong, Miqiu; Lv, Yadong; Huang, Yajiang; Yang, Qi; Li, Guangxian
Graphical abstract: Highlights: The branched PLA simultaneously exhibits extremely robust melt strength and low shear viscosity. The long-chain branches are uniformly dispersed on the backbone of PLA. The branched PLA shows super-robust foamability with volume expansion ratio of 72.9-fold. The branched PLA displays super-high heat resistance up to 155.1 °C. Abstract: Poor melt strength and crystalline properties are the key barrier for polylactide (PLA) toward broader applications. Long chain branched PLA (LCB-PLA) with high foamability and heat resistance are prepared by employing dual-functional 4-vinylbenzyl glycidyl ether (VBGE) as branching coagent with cyclic peroxide. As a result, the branched chains with same length of original PLA chains are uniformly dispersed on PLA backbones via both the free-radical grafting reaction of the vinyl group in VBGE with one PLA backbone and end-group reaction of the epoxy group in VBGE with the carboxyl group of the other PLA chain. Not only the significantly enhanced foamability and heat resistance of LCB-PLA induced by the largely improved melt strength and crystallization performance but also the excellent processing flowability due to a relatively slight increase in the shear viscosity are found. Specifically, as compared to the pure PLA, the expansion ratio of LCB-PLA with 0.6 wt% VBGE is increased by 17.4 times, and the Vicat softening temperature is enhanced by 95.5 °C. Thus, this study paves a novel one-step continuous strategy to design LCB-PLA with ultrahigh foamability and heat resistance, which is valuable for the large-scale popularization of foamed PLA packaging products.